Changes in toxic elements content of soil after sewage sludge treatment in energy willow plantation - Aranyos, Tibor József; Makádi, Marianna; Tomócsik, Attila (Acta Agraria Debreceniensis, 2012)
The primary purpose of our experiment was the solution of municipal excess sludge treatment by a renewable energy resource used willow (Salix viminalis L.) plantation. Tests were carried out to state whether the applied sewage sludge has caused any accumulation of the toxic elements in the studied soil layers, and - based on the results –to see whether the plantation is suitable for the treatment of municipal sewage sludge.The excess sludge (sludge before dewatering) is beneficial for the willow, because it contains a 3–5% dry matter and therefore, a lot of water, too. This high water content ensures the high water amount needed for the intensive growth of the willow. On the other hand, the wastewater treatment plant can save the dewatering cost which corresponds to about 30% of the water treatment process costs. The amounts of the sprinkled sewage sludge were calculated on the basis of its total nitrogen content. Treatments were the followings: control, 170 N kg ha-1 year-1 and 250 N kg ha-1 year-1. The mean values of the toxic element concentrations in the sewage sludge did not cross the permitted limits of the land  accommodating.The measured toxic element values of the soil were compared to the limits of the 50/2001. (IV.3.) Government Regulation.The  sprinkled sewage sludge on the bases of the total N content did not cause accumulation of heavy metals in the soil and the treated plants were also healthy without any signs of toxicity.